2013
DOI: 10.1111/tmi.12212
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of influences on infant feeding strategies in women living with HIV in Cape Town, South Africa: a mixed methods study

Abstract: Abstractobjective To explore influences on infant feeding intentions and practices in women living with HIV in South Africa.methods Structured questionnaires were completed by 207 pregnant women and 203 post-partum women in Cape Town, South Africa. Concurrently, 34 semi-structured, qualitative interviews explored the influences on infant feeding strategies in women living with HIV.results Overall, 50% (104) of pregnant women intended to breastfeed and 22% (45) Other important influences included previous infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 14 publications
(21 reference statements)
4
26
0
8
Order By: Relevance
“…Having HIV infection was associated with decreased adjusted odds of an intention to breastfeed, with a proportion of women with HIV reporting an intention to formula feed because of fears of infecting their infants. Similar to other studies, higher levels of maternal education and discussing infant feeding intentions with others were associated with decreased adjusted odds of an intention to exclusively breastfeed [8, 20]. Zulliger et al [8] found that women with HIV, with lower levels of education, were more likely to express an intention to breastfeed.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Having HIV infection was associated with decreased adjusted odds of an intention to breastfeed, with a proportion of women with HIV reporting an intention to formula feed because of fears of infecting their infants. Similar to other studies, higher levels of maternal education and discussing infant feeding intentions with others were associated with decreased adjusted odds of an intention to exclusively breastfeed [8, 20]. Zulliger et al [8] found that women with HIV, with lower levels of education, were more likely to express an intention to breastfeed.…”
Section: Discussionsupporting
confidence: 68%
“…Similar to other studies, higher levels of maternal education and discussing infant feeding intentions with others were associated with decreased adjusted odds of an intention to exclusively breastfeed [8, 20]. Zulliger et al [8] found that women with HIV, with lower levels of education, were more likely to express an intention to breastfeed. Women with higher levels of education are likely to be employed and hence be able to afford infant formula [20].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Second, an individualized approach may be too cumbersome for healthcare workers to implement, and previous efforts to individualize infant feeding recommendations have led to confusion about feeding recommendations for both HIV-infected and HIV-uninfected women [1, 46, 5052]. Our results suggest that the individualized approach could lead to moderate benefits compared to the public health approach, but only when RR-RF is very low or very high or ARV availability is limited; some providers may already be individualizing feeding recommendation in such situations [50, 52]. The individualized approach is likely of minimal benefit at the intermediate values of RR-RF expected in most settings, or as programs scale up the availability of maternal ART under Options B/B+.…”
Section: Discussionmentioning
confidence: 99%